2021
DOI: 10.1186/s12879-020-05711-2
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities for HIV testing in patients newly diagnosed with HIV in Morocco

Abstract: Background In Morocco, of the estimated 29,000 people living with HIV in 2011, only 20% were aware of their HIV status. More than half of diagnoses were at the AIDS stage. We assumed that people who were unaware of their infection had contacts with the healthcare system for HIV indicators that might prompt the healthcare provider to offer a test. The aim was to assess missed opportunities for HIV testing in patients newly diagnosed with HIV who accessed care in Morocco. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…There is a paucity of published data on missed opportunities in the MENA region. Similar to our findings, a study from Morocco reported that 69% of their 650-subject cohort had missed opportunities for HIV testing 15 . In contrast, studies from countries outside the MENA region such as Italy, Sweden, Germany and UK showed that 21–27% of newly diagnosed HIV subjects who sought medical care for ICs were not offered HIV testing 46 50 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There is a paucity of published data on missed opportunities in the MENA region. Similar to our findings, a study from Morocco reported that 69% of their 650-subject cohort had missed opportunities for HIV testing 15 . In contrast, studies from countries outside the MENA region such as Italy, Sweden, Germany and UK showed that 21–27% of newly diagnosed HIV subjects who sought medical care for ICs were not offered HIV testing 46 50 .…”
Section: Discussionsupporting
confidence: 91%
“…Providers have described insufficient time and resources, the laborious process of counseling and consent, as well as low provider-perceived risk of transmission as barriers to offering an HIV test 13 , 14 . Studies of missed opportunities for earlier diagnoses have shown that individuals with late presentations had often presented to healthcare settings several times, sometimes with indicator conditions (ICs) before an HIV test was eventually made 15 . Meanwhile, the presence of punitive laws and policies, such as the criminalization of sex work and same-sex sexual acts, in some countries deter individuals from seeking HIV testing 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, war had restricted the surveillance activities e.g., access to voluntary counseling and treatment (VCT) centers in Syria [ 62 ]. Therefore, many opportunities for HIV testing, based on at-risk behaviors or clinical signs, were missed [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…HIV and HCV testing can be performed by any physician both in hospitals and primary care facilities. Missed testing opportunities in both locations remain high (10)(11)(12)(13)(14)(15)(16), although some primary care educational interventions have improved screening rates (17,18). Nevertheless, among hospital noninfectious disease (ID) specialists, reports on such interventions are scarce.…”
Section: Introductionmentioning
confidence: 99%